2021
DOI: 10.3389/fnins.2021.655019
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Modality Transfer Method of Brain Imaging Based on Generative Adversarial Network

Abstract: Brain imaging technology is an important means to study brain diseases. The commonly used brain imaging technologies are fMRI and EEG. Clinical practice has shown that although fMRI is superior to EEG in observing the anatomical details of some diseases that are difficult to diagnose, its costs are prohibitive. In particular, more and more patients who use metal implants cannot use this technology. In contrast, EEG technology is easier to implement. Therefore, to break through the limitations of fMRI technolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…While there are many different types of GANs usually named based on their architectures, there is a tendency to assign a new name to every GAN even if the fundamental changes in the architecture are not significant. This review found that the most common types of GANs used were the cycleGAN used by 12 studies [ 15 , 17 , 48 , 51 , 55 – 57 , 65 , 66 , 79 , 84 , 110 , 133 ] followed by conditional GAN used by 8 studies [ 53 , 54 , 71 , 72 , 101 , 112 , 118 , 119 ], and Wasserstein GAN used by 7 studies [ 13 , 14 , 19 , 39 , 116 , 131 , 132 ]. Other types of GANs reported in more than one study were deep convolutional GAN, reported in three studies [ 20 , 93 , 140 ], unified GAN [ 21 , 49 ] reported in two studies, and Pix2Pix GAN, reported in two studies [ 32 , 133 ].…”
Section: Resultsmentioning
confidence: 99%
“…While there are many different types of GANs usually named based on their architectures, there is a tendency to assign a new name to every GAN even if the fundamental changes in the architecture are not significant. This review found that the most common types of GANs used were the cycleGAN used by 12 studies [ 15 , 17 , 48 , 51 , 55 – 57 , 65 , 66 , 79 , 84 , 110 , 133 ] followed by conditional GAN used by 8 studies [ 53 , 54 , 71 , 72 , 101 , 112 , 118 , 119 ], and Wasserstein GAN used by 7 studies [ 13 , 14 , 19 , 39 , 116 , 131 , 132 ]. Other types of GANs reported in more than one study were deep convolutional GAN, reported in three studies [ 20 , 93 , 140 ], unified GAN [ 21 , 49 ] reported in two studies, and Pix2Pix GAN, reported in two studies [ 32 , 133 ].…”
Section: Resultsmentioning
confidence: 99%
“…GANs have demonstrated success in augmenting EEG data for motor imagery, P300-based applications, emotion recognition, and epileptic seizure detection and prediction. It is noteworthy here that a few studies on EEG-based image generation have been excluded from this article such as [ 95 – 98 ], and [ 99 , 100 ]. The main justification for this elimination is that these studies mainly use GAN methods for image generation and EEG signals were being used as an auxiliary input without applying GAN to the EEG data itself.…”
Section: Discussionmentioning
confidence: 99%
“…There are multiple potential benefits to this, including decreased need for multimodal studies, reduced acquisition time and radiation exposure, and increased availability of appropriate imaging in cases where there is limited access to multimodal imaging, e.g., in a clinical scenario where a certain imaging modality (such as MRI) might be optimal for diagnosis or treatment planning but only another modality (such as CT) is available to the patient. The predominant type of GAN used for this application is CycleGAN [21,[90][91][92][93].…”
Section: Image-to-image Translationmentioning
confidence: 99%